DIAPHYSEAL NUTRIENT FORAMINA IN DRIED HUMAN ADULT LONG BONES OF LOWER LIMB IN PAKISTAN - Afzal, Ejaz; Sherin, Fatima; Khan, Omair; Siddiqui, Noaman Hussain (Journal of Ayub Medical College Abbottabad, 2017)
Background: osteogenesis needs circulation of blood in the bones. Bone growth, repair of fracture, maintenance of bone vitality and other injures also need blood circulation in proper way. Blood is allowed to flow via holes in the diaphysis, which are called as nutrient foramina. Methods: The cross-sectional study was done in the department of Anatomy, Ayub and Khyber Medical College (Osteology Sections). The aim was to observe diaphyseal nutrient foramina in the human long bones of the lower limb. The study was done on 90 long bones of lower limb consisting of 30 femora, 30 tibiae and 30 fibulae. Of all these bones, sex was not determined. All the bones were macroscopically observed. For the number of the foramina, simple counting was done. The foraminae 1 mm away from the borders were counted. All positions were seen macroscopically. For direction and obliquity, stiff wire was used. Results: We studied 90 long bones of lower limb. About 80% of long bones of lower limb showed single nutrient foramina. About 18% of lower limb long bones showed two nutrient foraminae. In cases of femora nutrient foraminae were directed proximally. In cases of fibulae and tibiae most of the foramina were directed distally. Conclusion: the study has provided additional information on the foramina index, morphology and topography of the nutrient foramina. In the lower limb long bones, the anatomical data is important for the clinicians as the micro-vascular bone transfer is becoming popular. This morphological data can be used by the forensic experts in identification through different landmarks in bones development giving an aid in medicolegal work. Keywords: Micro-vascular bone transfer; topography; femora; tibiae; proximally; distally; osteology; diaphysis